Learning defects in Drosophila growth restricted chico mutants are caused by attenuated adenylyl cyclase activity. Issue 1 (December 2016) - Naganos, Shintaro; Ueno, Kohei; Horiuchi, Junjiro; Saitoe, Minoru
Abstract Background Reduced insulin/insulin-like growth factor signaling (IIS) is a major cause of symmetrical intrauterine growth retardation (IUGR), an impairment in cell proliferation during prenatal development that results in global growth defects and mental retardation. InDrosophila, chico encodes the only insulin receptor substrate. Similar to other animal models of IUGR, chico mutants have defects in global growth and associative learning. However, the physiological and molecular bases of learning defects caused bychico mutations, and by symmetrical IUGR, are not clear. Results In this study, we found thatchico mutations impair memory-associated synaptic plasticity in the mushroom bodies (MBs), neural centers for olfactory learning. Mutations inchico reduce expression of therutabaga -type adenylyl cyclase (rut ), leading to decreased cAMP synthesis in the MBs. Expressing arut + transgene in the MBs restores memory-associated plasticity and olfactory associative learning inchico mutants, without affecting growth. Thuschico mutations disrupt olfactory learning, at least in part, by reducing cAMP signaling in the MBs. Conclusions Our results suggest that some cognitive defects associated with reduced IIS may occur, independently of developmental defects, from acute reductions in cAMP signaling.